Distant learning evolution in the higher educational institutions in Canada - Котова, А. В.; Сердюк, В. М. (Scientific notes of the pedagogical department, 2019)
The article is devoted to the development of distant learning in the higher educational institutions in Canada. It is established that the development of distant learning in Canada was due to long distances between cities on the one hand and the need to improve the education of qualified employees on the other hand. It should be noted that the origin of distant education in the world is associated with the name of Isaac Pitman, who began teaching stenography by mail in the UK in 1840. After that, this form quickly spread in Canada, the United States and the United Kingdom. The form of distant learning education was developed for students who did not have the opportunity to attend lectures and practical classes, and who lived far away from institutions of higher education. Accordingly, most of the study material was to be learnt independently, while the function of higher education institutions was to direct students’ educational activities, develop special programs and assignments, and consult students during the inter-sessional period. First, distance learning was introduced in 1889, in the University of McGill, Montreal. There was a need to improve the skills of teachers, especially from distant regions, who had to acquire deep knowledge, but didn’t have the possibility to come to university. For this purpose special programs and a number of methodical assignments for independent work and self control were developed there. To facilitate the acquiring of knowledge educational television and radio programs were broadcasted in the country. Approaches to the organization of distant learning in Canada changed in the late 1990s, when the Internet connection was widely spread.